Bioindication assessment of the waters of the Chernaya River - A. K. Jiyenbekov; S. B. Nurashov; E. S. Sametova; G. B. Dzhumakhanova (Проблемы ботаники Южной Сибири и Монголии, 2021)
The purpose of the current study was to identify the species indicators of the communities of the ChernayaRiver and to assess the water quality by bioindication methods. During the summer field trips in 2019–2020 on the territoryof the Zhongar–Alatau Natural State Reserve within the framework of the special purpose funding program № BR05236546“Implementation by the state botanical gardens of the priority scientific and practical tasks of the global strategy for plantconservation as a sustainable system for maintaining biodiversity” (head, Dr. G. T. Sitpayeva). In the course of the study,algae were sampled from the Chernaya River, and their species composition was studied A total of 94 species and varietiesof algae from four divisions were found. Analysis of indicator types by water properties: temperature, oxygen saturation,organic pollution, salinity, trophic state of water and the type of nutrition of algae species has been revealed. This was thefirst experience of implementing a bioindication approach to the environmental assessment of the water quality of thisriver. The most significant types of diatoms strongly predominated in different studied places of the river. It was revealedthat the algae species can characterize the composition of the river as slightly alkaline, slightly saline, moderate, medium –acidified water with low organic pollution. Algae communities are mainly represented by benthic and planktonic – benthicautotrophic species. Statistical analysis of species – mediated relationships has shown that most species prefer to survive incommunities with complex structures formed in poorly polluted organic waters.